(untitled) (TEST BioLaw Journal - Rivista di BioDiritto, 2020)
The present agrifood production system can not sustainably feed the present and the future world population, and it needs to be re-designed in a circular economy perspective. Insects, with their ability to grow on agrifood by-products and wastes, yielding highly nutritious, and safe, food and feed ingredients, can help the transition to a more sustainable agrifood production. In the European Union, since 2018 insects have been designed as novel food, and their use as feed ingredients has been regulated. Insects are slowly, but steadily, becoming an integrated part of our agrifood system.